ENVIRONMENTAL IMPACT ANALYSIS OF HEAVY METAL CONCENTRATIONS IN WASTE MATERIALS USED IN ROAD CONSTRUCTION (Advances in Civil and Architectural Engineering, 2021)
Use of solid waste in place of conventional materials in civil engineering structures preserves natural resources and energy and avoids expensive and/or potentially harmful waste disposal. Many studies are investigating the application of waste materials in civil engineering structures. However, in an effort to find out new areas of waste materials utilization, the environmental impact of the installation of such materials in building structures often remains neglected. This study focused on the environmental aspect of the application of currently investigated waste materials in Croatia with an emphasis on heavy metal content. Heavy metal concentration in steel slag, river sediment, and biomass ash was measured, and the possibility of their use in road construction in accordance with currently valid legislation was assessed.